FTA121 : Academic writing / College of Creative Arts - UiTM, College of Creative Arts
This course equips the students with the basics of academic writing process.This subject rest on the mechanism of research. It helps the students to identify keywords of topic given and guides them to narrow the scope of their interest into an achievable research topic. Researching the given topic involves identifying sources of reference in books, journals, magazines or the internet. Thus, the process will further to the process of writing and analyzing the sources, data or conceptual found through the literature reviewing process into a comprehensible piece with clarity and creativity. Students will also be required to assess, rewrite, quote and revise their writing piece. This will ultimately assist them in producing a worthwhile research, written in the standard academic format.